Study on the Interaction of Amoxicillin and DNA by Spectroscopic and Voltammetric Studies - Hajian, R.; Shams, N.; Azarinezhad, N. (Asian Journal of Chemistry, 2010)
Spectrophotometric and voltammetric methods were used to probe the interaction of antimicrobial drug amoxicillin with calf thymus DNA (CT-DNA). Binding constants (K) and binding site sizes (s) were determined from the voltammetric data, i.e., shifts in potential and changes in limiting current with the addition of CT-DNA. Amoxicillin showed appreciable electrostatic binding to CT-DNA in solution with K = 2.7 × 104 mol-1 L and s =0.42 bp. Methylene blue have been used as a probe for distinguish the mode of interaction between drug and CT-DNA. The voltammetric behaviour of amoxicillin has been investigated at a glassy carbon modified with multiwalled carbon nano tubes (MWCNTs) using cyclic voltammetry. The apparent transfer coefficients (a) and the number of electron transferred (n) of amoxicillin in the absence and presence of CT-DNA have determined using anodic Tafel plots of amoxicillin and amoxicillin- CT-DNA adduct on the surface of modified glassy carbone electrode. The slopes of the calibration curves for amoxicillin in the absence and presence of CT-DNA are significantly differing with each other that demonstrate a mode of interaction. Both UV-vis spectrophotometry and cyclic voltammetry studies confirmed the groove binding interaction between amoxicillin and CTDNA.